Mapping the risk perception and communication gap between different professions of healthcare providers in cancer care: a cross-sectional protocol. Issue 9 (3rd September 2015) - Stub, Trine; Musial, Frauke; Quandt, Sara A; Arcury, Thomas A; Salamonsen, Anita; Kristoffersen, Agnete; Berntsen, Gro
Abstract : Introduction: Studies show that patients with cancer who use complementary and alternative medicine (CAM) have a poorer survival prognosis than those who do not. It remains unclear whether this is due to a priori poorer prognosis that makes patients turn to CAM, or whether there is a factor associated with CAM use itself that influences the prognosis negatively. Healthcare providers should assist patients in safeguarding their treatment decision. However, the current non-communication between CAM and conventional providers leaves it up to the patients themselves to choose how to best integrate the two worlds of therapy. In this study, an interactive shared decision-making (SDM) tool will be developed to enable patients and health professionals to make safe health choices. Methods and analysis: We will delineate, compare and evaluate perception and clinical experience of communication of risk situations among oncology experts, general practitioners and CAM practitioners. To accomplish this, we will develop a pilot and implement a large-scale survey among the aforementioned health professionals in Norway. Guided by the survey results, we will develop a β-version of a shared decision-making tool for healthcare providers to use in guiding patients to make safe CAM decisions. Ethics and dissemination: Participants must give their informed and written consent before inclusion. They will be informed about the opportunity to drop out from the study followed by deletion of all data registered. The study needs no approval from The Regional Committee for Medical and Health Research Ethics because all participants are healthcare professionals. Results from this study will be disseminated in peer-reviewed medical journals.